Efektivitas Instagram dalam Meningkatkan Minat Kunjungan Wisatawan di Daerah Istimewa Yogyakarta - Ani Wijayanti (Lasigo Akademia Indonesia, 2021)
Promotion and marketing through social media becomes a strategic issue during a pandemic, due to there are various restrictions on activities. One of the popular social media is Instagram. Instagram provides features for editing photos, editing videos, messaging, sharing photos and videos, and sharing reviews or reviews. The Yogyakarta Special Region tourism office (D.I.Y) uses Instagram as the main social media in the promotion and marketing of tourist destinations in D.I.Y. This study aims to review the effectiveness of the use of Instagram by measuring the extent to which the influence of the ability of tourists to access Instagram and the quality of Instagram on the interest in tourist visits in the Special Region of Yogyakarta. The study used a quantitative descriptive approach by conducting a survey of 200 respondents. Data measurement used a 5-point Likert scale and analyzed using linear regression techniques. The results showed that there was a significant positive influence between the ability of tourists to access Instagram and the quality of Instagram on the visiting interest, both partially and simultaneously. The quality of Instagram has a dominant influence of 40%, compared to the ability of tourists to access Instagram, which is 19.9%. The variable access ability and quality of Instagram contributed 53.2% to the visiting interest, while the remaining 46.8% was explained by other variables not involved in this study.